PERSPEKTIF MAHASISWA PENDIDIKAN AGAMA ISLAM UNIVERSITAS ISLAM SUNAN KALIJAGA TENTANG KASUS KEKERASAN SEKSUAL DI PERGURUAN TINGGI - Miladina Silvia; Dwi Ratnasari; Rohmatun Lukluk I (Jurnal Dakwah Tabligh, 2024)
The purpose of this qualitative study is to determine how Islamic Religious Education students view sexual violence and cases instances sexual assault that take place in higher education settings and investigate more how students react to those who have been sexually assaulted. The large number of cases of sexual violence that occur in universities are caused by power relations as someone who has more power over students so that these actions can occur. Apart from that, sexual violence can also occur due to a lack of education for students regarding self-protection and ways to increase awareness of cases of sexual violence which can attack anyone at any time and be carried out by anyone, even those closest to us. This research will be carried out on the campus of the Sunan Kalijaga State Islamic University, Yogyakarta, where several students' perspectives and understanding will be sought regarding cases of sexual violence that occur on the campus of the Sunan Kalijaga State Islamic University and also understanding of cases of sexual violence on campuses in Indonesia. This study employs descriptive methodologies and a qualitative approach in field research. This research was carried out using a phenomenological and normative approach which aims to describe how students majoring in Islamic religious education who also have a santri background understand about incidents of sexual assault that took place on campus of UIN Sunan Kalijaga Yogyakarta. Research data was obtained using 3 types of student respondents, namely fundamentalist students, activist students and traditionalist students. Each of course has a different point of view.